2007
DOI: 10.1056/nejmoa070829
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Medical Therapy with or without PCI for Stable Coronary Disease

Abstract: As an initial management strategy in patients with stable coronary artery disease, PCI did not reduce the risk of death, myocardial infarction, or other major cardiovascular events when added to optimal medical therapy. (ClinicalTrials.gov number, NCT00007657 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

94
1,934
11
131

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 4,072 publications
(2,170 citation statements)
references
References 44 publications
94
1,934
11
131
Order By: Relevance
“…Despite these guidelines for management of stable obstructive CAD, previous work from our group and others has demonstrated that OMT is underused in this patient population 1, 2, 14, 16. In contrast, there are no definitive guidelines for medical management of nonobstructive CAD, and there is substantial uncertainty as to what constitutes OMT in a population of patients with nonobstructive CAD.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite these guidelines for management of stable obstructive CAD, previous work from our group and others has demonstrated that OMT is underused in this patient population 1, 2, 14, 16. In contrast, there are no definitive guidelines for medical management of nonobstructive CAD, and there is substantial uncertainty as to what constitutes OMT in a population of patients with nonobstructive CAD.…”
Section: Discussionmentioning
confidence: 96%
“…There are clear guidelines for medical management of stable obstructive CAD, which include aspirin, ACE‐I, or ARB in appropriate patients, an anti‐ischemic agent, and statins 14. Despite these guidelines for management of stable obstructive CAD, previous work from our group and others has demonstrated that OMT is underused in this patient population 1, 2, 14, 16.…”
Section: Discussionmentioning
confidence: 99%
“…The seminal study by Gould et al reported that hyperemic flow begins to decline in the presence of stenosis with a reduction in diameter larger than 50% 1. This cut‐off value has been used for the threshold of inducible ischemia; therefore, it is accepted as the gold standard for guiding revascularization, validating noninvasive testing, and evaluating outcomes after revascularization strategies 2, 3, 4. However, cumulative evidence suggests that angiographically determined anatomical stenosis severity often underestimates or overestimates the functional significance of lesions 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant reduction in intracellular Na +  concentration inhibits partially the Na + /Ca ++ exchange current, preventing the deleterious effect of intracellular Ca ++  overload under the trigger of ischemia. This indirect decrease in intracellular Ca ++  concentration is responsible for the well‐documented antianginal effect of ranolazine 11, 12. In the field of clinical studies, ranolazine is presented as an effective, well‐tolerated, and safe drug, in patients with coronary artery disease and residual reversible ischemia 13, 14.…”
Section: Discussionmentioning
confidence: 99%